Block of N-methyl-D-aspartate-activated current by the anticonvulsant MK-801: selective binding to open channels. - Huettner, J E (1988)
Whole-cell and single-channel recording techniques were used to study the action of the anticonvulsant drug MK-801 [(+)-5-methyl-10,11-dihydro-5H-dibenzo[a,d]- cyclohepten-5,10-imine maleate) on responses to excitatory amino acids in rat neocortical neurons in cell culture. MK-801 caused a progressive, long-lasting blockade of current induced by N-methyl-D-aspartate (N-Me-D-Asp). However, during the time that N-Me-D-Asp responses were inhibited, there was no effect on responses to quisqualate or kainate, suggesting that N-Me-D-Asp receptors and kainate/quisqualate receptors open separate populations of ion channels. Binding and unbinding of MK-801 seems to be possible only if the N-Me-D-Asp-operated channel is in the transmitter-activated state: MK-801 was effective only when applied simultaneously with N-Me-D-Asp, and recovery from MK-801 blockade was speeded by continuous exposure to N-Me-D-Asp [time constant (tau) approximately equal to 90 min at -70 to -80 mV]. Recovery from block during continuous application of N-Me-D-Asp was strongly voltage dependent, being faster at positive potentials (tau approximately equal to 2 min at +30 mV). Mg2+, which is thought to block the N-Me-D-Asp-activated ion channel, inhibited blockade by MK-801 at negative membrane potentials. In single-channel recordings from outside-out patches. MK-801 greatly reduced the channel activity elicited by application of N-Me-D-Asp but did not significantly alter the predominant unitary conductance. Consistent with an open-channel blocking mechanism, the mean channel open time was reduced by MK-801 in a dose-dependent manner.